Corpus Driven Analysis of the Coronavirus Prevention Handbook - Ayu Humairoh Hakim; Zamzani Zamzani (Badan Pengembangan dan Pembinaan Bahasa, 2023)
Information about coronavirus prevention is important to know because coronavirus as the global pandemic after being designated by the World Health Organization (WHO) for four years. The aim of this article is to find out linguistic evidences from the lexical aspects such as lexical items, lexical categories, lexical cohesion and lexical bundles. Then analyzed it through corpus-driven analysis using AntConc software, this software is employed to process the data. This research uses a mix method and concurrent embedded model, after that downloading the data, observation and documentation as technique of collecting data, while the technique of analysis data use converting and compiling data, reduction data classification data and display data. The results of the quantitative and qualitative analyses show the result of corpus driven analysis through AntConc show the most common of lexical and syntactical aspects such as word classes, and sentences patterns used in the coronavirus prevention handbook. AbstrakInformasi tentang pencegahan virus korona penting untuk diketahui, karena virus korona sebagai pandemi global setelah ditetapkan oleh Organisasi Kesehatan Dunia (WHO) setelah berjalan selama satu tahun. Tujuan dari artikel ini adalah untuk mencoba mencari tahu bukti linguistik dari aspek leksikal dan sintaksis. Kemudian dianalisis melalui analisis berbasis korpus menggunakan aplikasi Antconc, perangkat lunak ini digunakan untuk memproses data. Penelitian ini menggunakan metode campuran dan model campuran tidak berimbang, setelah itu mengunduh data, observasi, dan dokumentasi sebagai teknik pengumpulan data, adapun teknik data analisis menggunakan data konversi dan penyusunan data, data klasifikasi data pengurangan dan data tampilan. Hasil analisis kuantitatif dan kualitatif menunjukkan hasil AntConc dan menunjukkan aspek leksikal dan sintaksis yang paling umum seperti kelas kata, dan pola kalimat yang digunakan dalam buku pegangan pencegahan virus korona.